Description of the poet Njrbnh poetic in his hair In the second century AH (Journal of the College of Basic Education, 2022)
The topic (the poet's description of his poetic experience in his poetry in the second century AH) did notHe takes his right to study and analysis, and we want that the poet's self-uniqueness is to say: I want toI create something that no one else has created, or we say that imagination, reason, and the powers of the soul come together in order to complete itcreativity and creation; However, we did not proceed from the sources of criticism; Rather, we proceeded from the collections of poetsThe tongue of her condition says why should the poet always be creative? The research answers the following questionsWhen difficult to say poetry on the poet? And when does poetry obey him? When does he find it hard to write?And when does he find pleasure in it? Does the poet's beauty and ugliness affect the topics of his poetry? And when is itPoetry admiration? And when does he play poetry? And when does he like poetry?